Non-orthogonal stagnation point flow of Maxwell nano-material over a stretching cylinder. (January 2021) - Abbasi, A.; Mabood, F.; Farooq, W.; Hussain, Z.
Abstract: Oblique stagnation point flow of incompressible Maxwell nanofluid past a stretching cylinder with active and passive controlled nanoparticles concentration condition is discussed numerically. The suitable coordinate decomposition reduce the governing boundary layer equations into the system of nonlinear ordinary differential equations which are approximated by Keller box procedure for several values of pertinent parameters. The Numerical results are compared and validated with existing ones as particular cases and found to be an excellent agreement. Velocity profile and lines of flow are sketched to discuss the Obliqueness of the flow. The temperature and concentration profiles drawn to illustrate the influence of involved parameters also variations in local Nusselt and Sherwood numbers are presented through tabular data. It is observed that the behavior of tangential velocity for the viscoelastic fluid and concentration of nanoparticles against thermophoresis diffusion over the cylinder are quite opposite when compared with the results over flat sheet. The temperature distribution and concentration of nanoparticles decreases with elasticity of the fluid.